Efficient production and characterization of melanin from Thermothelomyces hinnuleus SP1, isolated from the coal mines of Chhattisgarh, India - Pandey, Shalini; Meshram, Vineet; Yehia, Hany M.; Alzahrani, Abdulhakeem; Akhtar, Nadeem; Sur, Arunima (Frontiers in Microbiology, 2024)
In the present study, fungi were isolated and screened from barren land of south-eastern coal fields (SECL). Out of 14 isolated fungi, only three fungal isolates exhibited pigmentation in screening studies. The isolated fungal strain SP1 exhibited highest pigmentation, which was further utilized for in-vivo production, purification, and characterization of melanin pigment. Physical and chemical properties of the fungal pigment showed insolubility in organic solvents and water, solubility in alkali, precipitation in acid and decolourization with oxidizing agents. The physiochemical characterization and analytical studies of the extracted pigment using Ultraviolet visible spectroscopy, FTIR (Fourier transform infrared) confirmed as a melanin pigment. The melanin producing fungus SP1 was identified as Thremothelomyces hinnuleus, based on 18S-rRNA sequence analysis. Furthermore, to enhance melanin production, a response surface methodology (RSM) was employed, specifically utilizing the Central Composite Design (CCD). This approach focused on selecting the efficient growth as well as progressive yield parameters such as optimal temperature (34.4°C), pH (5.0), and trace element concentration (56.24 mg). By implementing the suggested optimal conditions, the production rate of melanin increased by 62%, resulting a yield of 28.3 mg/100 ml which is comparatively higher than the actual yield (17.48 ± 2.19 mg/100 ml). Thus, T. hinnuleus SP1 holds great promise as a newly isolated fungal strain, which could be used for industrial production of melanin production.